Towards recovery-oriented psychosocial interventions for bipolar disorder: Quality of life outcomes, stage-sensitive treatments, and mindfulness mechanisms. (March 2017) - Murray, Greg; Leitan, Nuwan D; Thomas, Neil; Michalak, Erin E; Johnson, Sheri L; Jones, Steven; Perich, Tania; Berk, Lesley; Berk, Michael
Abstract: Current adjunctive psychosocial interventions for bipolar disorder (BD) aim to impact illness course via information sharing/skill development. This focus on clinical outcomes contrasts with the emergent recovery paradigm, which prioritises adaptation to serious mental illness and movement towards personally meaningful goals. The aim of this review is to encourage innovation in the psychological management of BD by considering three recovery-oriented trends in the literature. First, the importance of quality of life as a target of recovery-oriented clinical work is considered. Second, the recent staging approach to BD is described, and we outline implications for psychosocial interventions tailored to stage. Finally, we review evidence suggesting that mindfulness-based psychosocial interventions have potential across early, middle and late stages of BD. It is concluded that the humanistic emphasis of the recovery paradigm provides a timely stimulus for development of a next generation of psychosocial treatments for people with BD. Highlights: The recovery paradigm encourages new approaches to psychological therapies for bipolar disorder. Subjective quality of life can be reliably quantified, and is a key person-centric outcome measure in bipolar disorder. Response to psychological treatment appears to be moderated by stage of disorder, and new therapies should consider stage-tailoring. Mindfulness-based interventions target vulnerabilities that are important across stages of bipolar disorder, and warrant further research.